History of English Literature in Pre-Post Independence India: Exploring the Evolution of Indian English Literature (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The main theme of the current magazine, entitled History of English Literature in India before Independence It is considered fundamental. It addresses the different parts of the books when freedom. There has also been an attempt to connote the books of Mulk Raj Anand, Raja Rao and Manohar Malgonkar as a true Indian ostracism The title proposal is a humble attempt to discover the excellent work done by the prominent authors MRAnand, Raja Rao and Manohar Malgonkar in Indian writing in English. With this in mind, the purpose of this research is to review his modified strategies used to convey perspective on life. It also reflects the particular highlights of his books and the representative importance of anecdotal work, temperament, tone, and special methodology used in describing Indian English today. To show how English writing began in India before 1920 and how it was created in India, we first saw it in Section I, entitled Introduction. In an article entitled History of Indian English Literature, do you present the revival of Indian writing? The reformers for example Aurobindo, Rammohan Roy, etc. And his commitment to the development of the Renaissance. The impact of writing in English in India is also discussed in depth in this article.